A time-periodic and reaction–diffusion Dengue fever model with extrinsic incubation period and crowding effects. (February 2020) - Zhang, Liang; Wang, Shuang-Ming
Abstract: Dengue fever is a typical mosquito-borne disease transmitted by Aedes aegypti and Aedes albopictus mosquitoes to human, which has become a major public health concern worldwide. In this paper, we incorporate the extrinsic incubation period (EIP) of dengue virus, spatial and temporal (seasonal) heterogeneity, crowing effect for host population into Dengue fever transmission, and propose a time-periodic and nonlocal delayed reaction–diffusion model of Dengue fever. The basic reproduction number R 0 is introduced for the model system, and it serves a threshold type parameter that determines the transmission dynamics of Dengue fever. Numerical simulations indicate the influence of the aforementioned virus factors on the spread of the disease.